2020
DOI: 10.3390/cells9112522
|View full text |Cite
|
Sign up to set email alerts
|

LIMD2 Regulates Key Steps of Metastasis Cascade in Papillary Thyroid Cancer Cells via MAPK Crosstalk

Abstract: Although papillary thyroid carcinoma (PTC) has a good prognosis, 20–90% of patients show metastasis to regional lymph nodes and 10–15% of patients show metastasis to distant sites. Metastatic disease represents the main clinical challenge that impacts survival rate. We previously showed that LIMD2 was a novel metastasis-associated gene. In this study, to interrogate the role of LIMD2 in cancer invasion and metastasis, we used CRISPR-mediated knockout (KO) of LIMD2 in PTC cells (BCPAP and TPC1). Western blot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The survival time of NSCLC patients with overexpression of LIMD2 was shorter than that of patients with lower expression, indicating that LIMD2 may serve as a therapeutic target in NSCLC [45]. Araldi et al found that LIMD2 may strengthen phosphorylation of kinases related to epithelial-mesenchymal transition (EMT) and invasion, and modulate the crucial steps in the metastatic cascade of thyroid cancer cells through the mitogen-activated protein kinase (MAPK) crosstalk [47].…”
Section: Qpcr-gapdh Ggagcgagatccctccaaaat Ggctgttgtcatacttctcatgg Discussionmentioning
confidence: 99%
“…The survival time of NSCLC patients with overexpression of LIMD2 was shorter than that of patients with lower expression, indicating that LIMD2 may serve as a therapeutic target in NSCLC [45]. Araldi et al found that LIMD2 may strengthen phosphorylation of kinases related to epithelial-mesenchymal transition (EMT) and invasion, and modulate the crucial steps in the metastatic cascade of thyroid cancer cells through the mitogen-activated protein kinase (MAPK) crosstalk [47].…”
Section: Qpcr-gapdh Ggagcgagatccctccaaaat Ggctgttgtcatacttctcatgg Discussionmentioning
confidence: 99%
“…Metastasis is a multistep process, which involves local invasion, intravasation, transport, extravasation, and colonization [88]. These steps require a series of genetic, biochemical, and morphological deregulations that are present in an evolutionarily conserved developmental program known as the epithelial-mesenchymal transition (EMT) [64,[89][90][91].…”
Section: Cancer-derived Exosomes Regulate Tumor Promotion and Progressionmentioning
confidence: 99%
“…During embryogenesis, the EMT (EMT type I) gives rise to mesoderm (responsible for the formation of muscle, bone, and connective tissues) during gastrulation and neural crest delamination (which results in glial cell, adrenal gland, and epithelial pigmented cell formation) [90,96]. In adult life, the EMT plays a key role in tissue re-epithelization during wound healing (EMT type II) [95,97,98] but, when inappropriately active, such as occurs in carcinogenesis (EMT type III), the EMT causes important disturbances in epithelial tissue homeostasis and integrity, leading to cancer cell spread and metastasis [89,99].…”
Section: Cancer-derived Exosomes Regulate Tumor Promotion and Progressionmentioning
confidence: 99%
See 2 more Smart Citations